EVALUASI APLIKASI SISTEM AUTOMASI PERPUSTAKAAN INLIS LITE DI PERPUSTAKAAN SARASWATI WIDHYOTAMA SMA NEGERI 1 KUTA - Sukmawati, Ni Made; Suhartika, I Putu; Kastawa, Made (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2017)
This research method is descriptive qualitative research. Technique of collecting data is doing observation at library, do interview to library officer, and documentation. Informants from this research are officers in the library at SMA N 1 Kuta. This research was conducted on June 2, 2017. Data analysis was done by grouping the results of interviews conducted by the authors with the librarians who test data using technology acceptance model or TAM (Technology Acceptance Model). The results of this study indicate that the application of INLIS Lite in the library of Saraswati Widhyotama SMA Negeri 1 Kuta is very helpful for librarians in the management of home subsystem libraries start reporting data of the procurement department and service section, and inputting books to the system. The library automation system application can simplify and simplify the work of library staff, overcoming the time limitations so that librarians can provide better services to library users. Although INLIS Lite application has a deficiency that is still error capacity and network that does not support, but it can be overcome by using Local Area. Keywords: INLIS Lite, automation, and TAM